Modelo de mejoramiento de borde urbano a través del concepto de ecobarrio en la UPZ 32 San Blas (2018)
In this approach, a model of improvement of urban edge is configured in the UPZ 32 San Blas of the locality 04 San Cristóbal in Bogotá, as a means of integration between the city and the forest reserve of the eastern hills, in order to control the illegal expansion on them, through the articulation of spatial and socioeconomic strategies of a sustainable nature that allows its occupants to advance socio-economic and cultural dynamics in the sector according to the needs. This project aims to create a cultural center which has a library, theater, auditoriums,exhibition halls and a playroom among others. For the development of different cultural and sports activities. Within the proposal, a sustainable neighborhood eco is proposed; which is aimed at populations of forest ranger families and displaced peasants. They are integrated with the vegetation of the hill, through an ecological restoration program with native vegetation, together with a housing program of social interest and mixed housing in height that offers a trade in the first floors and public space appropriate to their needs